Diversidade genética e filogeografia das espécies Hoplias malabaricus (Bloch, 1794) e Prochilodus lacustris Steindachner, 1907 no Nordeste do Brasil - Piorski, Nivaldo Magalhães (Universidade Federal de São Carlos, 2010)
The State of Maranhão is considered as a transitional area between northeastern semiarid and amazonian rainforest. Various perennial rivers such as the rivers Parnaíba, Itapecuru, Mearim, Pindaré and Gurupi are found in Maranhão. Distribution patterns analysis indicated the region as an endemism area for Neotropical freshwater fishes. However, only few studies have been performed in the region. Therefore the relationships between the hidrographic set and the respective neighbour areas are not fully comprehended. One complication is the insufficient cientific knowledge about the endemism level in the region due to insufficient establishment of taxonomic bounds for several species in the area. This study examines the hypothesis that freshwater fishes from Maranhão rivers are valid taxonomic unities, and whether its hydrographic set can be considered as an endemism area for Neotropical fishes. The study is focused on the analsis of genetic differentiation of Hoplias malabaricus and Prochilodus lacustris. The geographic variation of H. malabaricus was studied using sequences of the DNAmt control region as well by geometric morphometrics. Besides the mitochondrial marker, the variation analyses of P. lacustris employed sequences of the S7 intron 1. Both species exhibited high genetic variability which may be related to its own ecological features. The genetic diversity of H. malabaricus, a sedentary species, is influenced by drainage architeture. On the other hand, the migratory behavior of P. lacustris and the results obtained had suggested that the variability found was influenced by historical factors. Because the most resolution of the P. lacustris data, the molecular clock hypothesis was tested and divergence times between populations sampled were estimated. These estimates matching with geological informations enabled us to identify several putative events that may play an important role in differentiation of the maranhense ichthyofauna. Under the taxonomic point of view, the hypothesis that H. malabaricus is a species complex was reinforced and the analyses suggested that putative criptic species occur in the region. The P. lacustris specimens constitute a taxonomic unit, but did not support the hypothesis that the species is endemic for the Parnaíba and Mearim rivers. Considering these results, we suggest that the most closely indication of endemism areas could be the ecoregions established by Secretaria de Recursos Hídricos from Ministério do Meio Ambiente.
Genetic diversity and phylogeography of the species Hoplias malabaricus (Bloch, 1794) and Prochilodus lacustris Steindachner, 1907 in northeastern Brazil
Keywords: Genética de populações; Região neotropical; Peixe de água doce; Variabilidade genética; Áreas de endemismo; Diversidade genética; Morfometria geométrica; Neotropical region; Brazil northeastern; Freshwater fishes; Genetic diversity; Phylogeography; Endemism areas; Molecular clock; Geometric morphometrics; CIENCIAS BIOLOGICAS::GENETICA